Clinical Results of Total Knee Megaprosthesis for Bone Tumors Around the Knee - Erenler, Mert; Babacan, Muharrem; Botanlıoğlu, Hüseyin; Kaynak, Gökhan; Güven, Mehmet Fatih; Şeker, Ali; Davulcu, Cumhur Deniz; Özşahin, Mahmut Kürşat (Cerrahpaşa Medical Journal, 2024)
Objective: Bone and soft tissue tumors have high mortality and morbidity rates. With new improvements in adjuvant–neoadjuvant therapies and new endoprosthesis designs, limb salvage surgery methods became more popular than amputations. The aim of our study was to evaluate the clinical and radiological results of patients who underwent surgery due to tumors around the knee with megaprosthesis. We also compared hinged and rotational hinged megaprosthesis to determine if they have advantages over each other. Methods: This study has a cohort design. Thirty-one patients who had been operated between 2000 and 2018 by a single surgeon with knee megaprosthesis were evaluated using International Limb Salvage Symposium criteria (ISOLS score). Results: The 5-year survival rate for the prostheses was 46.2%. The overall Musculoskeletal Tumor Society (MSTS) score was 84.65% ± 9.94% (range: 54%-97%) (fair-excellent), and the ISOLS score was 86.60% ± 10.47% (range: 45%-100%) (poor-excellent). There were no significant differences between the scores according to prosthesis types. As the strength of straight leg lift increased, so did the emotional acceptance for both types of prostheses. Conclusion: Megaprosthesis is a good choice of treatment for tumors around the knee without decreasing life expectancy. Both hinged and rotational hinged prostheses can be used according to clinical needs. Cite this article as: Erenler M, Babacan M, Botanlıoğlu H, et al. Clinıcal results of total knee megaprosthesıs for bone tumors around the knee. Cerrahpaşa Med J. 2024;48(1):55-58.